Digital Narratives as a Means of Shifting Settler-Teacher Horizons toward Reconciliation - Bissell, Alexandra; Korteweg, Lisa (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
The Truth and Reconciliation Commission’s Calls to Action report (2015), in the section “Education for Reconciliation” (p. 7, #62–63), calls for the integration of Indigenous knowledge and teaching methods into the curriculum and for better preparation of teachers to deliver Indigenous content. Settler-teachers, however, have not been adequately prepared for this mission, nor are they well-prepared to teach Indigenous students. This article discusses a project of dual purpose in support of reconciliation: to give Indigenous students the opportunity to represent their Land-based dogsledding experiences as iMovie digital narratives and to give settler-teacher candidates direct experience for relationship-building in an indigenized context of education. Drawing upon theories of settler-colonialism, decolonization, and reconciliation in education, the article illustrates the imperative of immersing settler-teachers into contexts where Indigenous students self-representing their identities and Indigenous knowledge are at the centre of the curriculum.